Redenzione e perdizione tra Manzoni e Pirandello - Sgroi, Alfredo (Italogramma, 2021)
<span dir="ltr" style="left: calc(var(--scale-factor)*85.10px); top: calc(var(--scale-factor)*146.92px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.944774);" role="presentation">In this essay, a parallel reading of the works of Manzoni and Pirandello is carried out, <span dir="ltr" style="left: calc(var(--scale-factor)*85.10px); top: calc(var(--scale-factor)*160.72px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.97029);" role="presentation">placing the theme of redemption at the center of attention. The two writers, the first <span dir="ltr" style="left: calc(var(--scale-factor)*85.10px); top: calc(var(--scale-factor)*174.52px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.935303);" role="presentation">Catholic, the second nihilist and skeptical, <span dir="ltr" style="left: calc(var(--scale-factor)*296.93px); top: calc(var(--scale-factor)*174.52px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.883669);" role="presentation">start <span dir="ltr" style="left: calc(var(--scale-factor)*321.67px); top: calc(var(--scale-factor)*174.52px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.939026);" role="presentation">from the common observation t<span dir="ltr" style="left: calc(var(--scale-factor)*477.10px); top: calc(var(--scale-factor)*174.52px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.90679);" role="presentation">hat the <span dir="ltr" style="left: calc(var(--scale-factor)*85.10px); top: calc(var(--scale-factor)*188.32px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.917969);" role="presentation">world of men is dominated by evil. Thus <span dir="ltr" style="left: calc(var(--scale-factor)*281.33px); top: calc(var(--scale-factor)*188.32px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.90874);" role="presentation">it was born <span dir="ltr" style="left: calc(var(--scale-factor)*336.79px); top: calc(var(--scale-factor)*188.32px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.907462);" role="presentation">the need for a confrontation with the <span dir="ltr" style="left: calc(var(--scale-factor)*85.10px); top: calc(var(--scale-factor)*202.12px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.935157);" role="presentation">divine. In the <span dir="ltr" style="left: calc(var(--scale-factor)*151.70px); top: calc(var(--scale-factor)*202.12px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.884703);" role="presentation">Promessi Sposi<span dir="ltr" style="left: calc(var(--scale-factor)*225.53px); top: calc(var(--scale-factor)*202.12px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9585);" role="presentation">, in <span dir="ltr" style="left: calc(var(--scale-factor)*243.89px); top: calc(var(--scale-factor)*202.12px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.907591);" role="presentation">Lazzaro<span dir="ltr" style="left: calc(var(--scale-factor)*282.65px); top: calc(var(--scale-factor)*202.12px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.912535);" role="presentation">, in many short stories, Manzoni and Pirandello <span dir="ltr" style="left: calc(var(--scale-factor)*85.10px); top: calc(var(--scale-factor)*215.92px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.907853);" role="presentation">describe the path of redemption that can transform the life of men.